Parents Participation of Student Care System in Opportunity Expansion School Under the Office of Ubonratchathani Primary Educational Service Area 1 - Supasorn, Supawan (Journal of Dhamma for Life, 2026)
This research aimed to: 1) examine the level of parental participation in the implementation of the student support system in opportunity expansion schools under the Ubon Ratchathani Primary Educational Service Area Office 1; 2) compare parental participation classified by age, position, and educational level; and 3) investigate guidelines for enhancing parental participation in the student support system. The study employed a mixed-methods research design. The sample consisted of 341 participants, including 15 school administrators, 30 teachers, and 296 parents from opportunity expansion schools under the Ubon Ratchathani Primary Educational Service Area Office 1. Research instruments included a questionnaire and a semi-structured interview form. The questionnaire demonstrated a high reliability coefficient of .98. Quantitative data were analyzed using percentage, mean, standard deviation, t-test, and one-way analysis of variance (F-test), while qualitative data were analyzed through content analysis. The findings revealed that: 1) the overall and individual aspects of parental participation in the implementation of the student support system were at a high level; 2) when comparing parental participation by age, no statistically significant differences were found, whereas differences based on position and educational level were statistically significant at the .01 level; and 3) the proposed guidelines for enhancing parental participation included establishing online communication channels for exchanging individual student information accurately and efficiently, utilizing accessible online student screening tools with clear interpretation processes, and organizing collaborative meetings between schools and parents to promote student development, solve problems, and provide appropriate referral support. The findings highlight the importance of collaboration between schools and parents in strengthening the effectiveness of the student support system and ensuring its alignment with contemporary educational contexts.